(untitled) (Global Journal of Science Frontier Research, 2014)
The current study was conducted on a deboned veal meat imported to the Kingdom of Saudi Arabia (KSA), and analyzed at Jeddah Food Control Laboratory (JFCL). The samples were collected routinely during 2013. The aim of this trial is to compare between effects of two sampling techniques; sponge swabbing and excision, on the capability of Salmonella recovery. A total of 900 samples of unknown infection status (150 individual samples × 3 analysts × 2 sampling methods) were examined for salmonella. Simultaneously, an artificial inoculation experiments of veal meat (n=120) were conducted. The international standard procedure for the detection of Salmonella (ISO 6579:2002) was the reference. Results show that the swab sampling technique was more representative, it resulted in higher isolation mean percentage of salmonella (97.8%) and (100%) of spiked samples, compared to excision percentage (86.7%) and (95%) of spiked samples. Percentages of swab and excision techniques of natural contaminated samples were positive for salmonella from the different analysts and ranged from 93.3% to 100% and from 70% to 100%, respectively. The average time for sampling by excision was significantly higher (5:10 minutes) than the corresponding time by swabbing technique (1:10 minute). Taking on consideration the daily workload pressure and the time required for sampling, the results illustrate that swabbing is superior to excision. This study suggests that swab sampling could be an alternative method for the detection of salmonella in meat on the basis of better recovery rate, accuracy, sensitivity and repeatability.